A Study of Social Learning for 8th – grade Students on Studying English at SMP Muhammadiyah 12 GKB - Qurniawan, Erik Okta; Anwar, Khoirul; Asmana, Candra Hadi (Universitas Muhammadiyah Gresik, 2020)
Social learning is an essential learning as a part of activities to change the behavior through public action. This study investigates a study of social learning for 8th grade on studying English at SMP Muhammadiyah 12 GKB. To guide students learning, the teacher serves the activity through modelling so that teacher must have known the students’ need before going to the class. It includes observational learning for the students in which affected their attention process, retention process, motor reproduction process, and also reinforcement process. It adopted theory of bandura toward social learning. The subject research is 32 students at 8th grade, it uses descriptive qualitative research during the observation and interview. The result of study described the transcript of conversation that involved in the classroom activity. Therefore this study aims to show social learning for 8th grade students on studying English at SMP Muhammadiyah 12 GKB